Federal credit programs - Commission on Money and Credit; Johnson, Stewart (Englewood Cliffs, N.J. : Prentice-Hall, 1963)
The book covers an analysis of the costs, credit standards, and credit terms empolyed in federal credit programs
A series of research studies prepared for the Commission on Money and Credit.
Includes bibliographical footnotes.
ucj 15/01/2019
Loans
Keywords: Monetary policy; Credit